1995
DOI: 10.1007/bf00213102
|View full text |Cite
|
Sign up to set email alerts
|

Induction of rat liver drug-metabolizing enzymes by tetrachloroethylene

Abstract: The effect of tetrachloroethylene on Phase I and II drug-metabolizing enzymes in rat liver was examined. Rats were treated orally with tetrachloroethylene daily for five days, at doses of 125, 250, 500, 1,000 and 2,000 mg/kg. The higher doses (> 500 mg/kg) of tetrachloroethylene induced the hepatic microsomal 7-pentoxyresorufin O-depentylase and 7-benzyloxyresorufin O-debenzylase activities associated with the CYP2B subfamily. 7-ethoxyresorufin O-deethylase activity was also induced about 2-fold compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Several chemicals have been reported to induce Gsts activities in fruit flies, such as benzo(a)pyrene (Cervello et al, 1992), oxadiaolone (Hunaiti et al, 1995), pentobarbital (Tang and Tu, 1995), tetrachloroethylene (Hanioka et al, 1995), and 2,3,7,8-tetrachlorodibenzo-p-dioxin (Schrenk et al, 1995). After long-term exposure of fruit flies to phenol, both cytosolic fractions and affinity column purified Gsts activities from phenol-treated fruit flies were all higher than those measured from wild type strain.…”
Section: June 2003mentioning
confidence: 44%
See 1 more Smart Citation
“…Several chemicals have been reported to induce Gsts activities in fruit flies, such as benzo(a)pyrene (Cervello et al, 1992), oxadiaolone (Hunaiti et al, 1995), pentobarbital (Tang and Tu, 1995), tetrachloroethylene (Hanioka et al, 1995), and 2,3,7,8-tetrachlorodibenzo-p-dioxin (Schrenk et al, 1995). After long-term exposure of fruit flies to phenol, both cytosolic fractions and affinity column purified Gsts activities from phenol-treated fruit flies were all higher than those measured from wild type strain.…”
Section: June 2003mentioning
confidence: 44%
“…Induction of Gsts could increase the amount of Gst proteins and elevate total enzyme activities (Bhagwat et al, 1998). Many chemicals have been reported as capable of inducing insect Gsts activities such as phenobarbital (Hayaoka and Dauterman, 1983;Lubet et al, 1992), pentobarbital (Tang and Tu, 1995), benzo(a)pyrene (Cervello et al, 1992), tetrachloroethylene (Hanioka et al, 1995), 2,3,7,8-tetrachlorodibenzo-p-dioxin (Schrenk et al, 1995, and oxadiaolone (Hunaiti et al, 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Also, it is suggested that tetrachloroethylene is metabolized by only phenobarbital-inducible P450 (Costa and Ivanetich 1980), whereas TCE is mainly metabolized by CYP2E1 or CYP2B1 /2 in the mouse and rat in vitro (Nakajima et al 1992). On the other hand, we reported that tetrachloroethylene markedly induces CYP2B1/2 in the rat liver (Hanioka et al 1995). This study indicated that TCE Figure 1.…”
Section: Resultsmentioning
confidence: 85%
“…It has been established that the activities of MFO are very low at birth but increase rapidly in adult and then subsequently decline in adult in all animal species including man [48][49][50][51][52]. For example, the cytochrome P450 1A mediated 2hydroxylation of biphenyl was present in neonatal rat and rabbit livers but this isozyme was not detected during adulthood [53,54].…”
Section: Agementioning
confidence: 99%